The Complex Relationship between Sunni Scholars and Sufi Mystics in the Middle Ages: A Case Study of al-‛Izz ibn ‛Abd al-Salām - Abboud, Saleh (Millah: Journal of Religious Studies, 2026)
This article interrogates the intricate nexus between Sunni jurisprudence and Sufi mysticism during the Ayyubid and early Mamluk eras, utilizing the preeminent jurist al-ʿIzz ibn ʿAbd al-Salām (d. 660 AH/1262 CE) as a focal point. The study addresses a core historiographical problem: the presence of discordant medieval narratives regarding al-ʿIzz’s formal affiliation with Sufi orders and his jurisprudential stance on Sufi praxis. To resolve this, the research pursues two pivotal questions: To what extent was al-ʿIzz genuinely integrated into Sufi circles, and how did his legal framework delineate the boundaries of permissible Sufi conduct and institutionalization? Employing a qualitative inductive methodology, the research systematically triangulates evidence from al-ʿIzz’s authenticated legal and ethical treatises (primary corpus) against diverse medieval biographical and hagiographical sources (secondary corpus/Ṭabaqāt). This analytical framework facilitates a critical distinction between established doctrinal positions and retroactive hagiographical attributions. The findings demonstrate that while al-ʿIzz maintained a profound intellectual rapport with orthodox Sufi luminaries—notably al-Shādhilī—and embraced the ethical-ascetic dimensions of Taṣawwuf, his verified writings articulate a rigorously selective endorsement. As a reformist jurist, he sanctioned Sufism only insofar as it remained tethered to Shari'ah-centric orthodoxy, while vehemently repudiating ritualistic innovations (Bidʿah) such as Samāʿ (ecstatic sessions). Consequently, the significance of this study lies in redefining al-ʿIzz not as a formal Sufi initiate, but as a paradigmatic “juristic gatekeeper.” These conclusions contribute to the broader discourse on medieval Islamic intellectual history by elucidating the mechanisms of scholarly policing of spiritual boundaries and the complexities of manuscript-based historical reconstruction.